The Effects of Multi-religious Traditions in The Formation of a Mixed Civilization of the Subcontinent, A Historical Study - Dr. Kulsoom Paracha; Dr. Munazza Hayat (jihat-ul-islam, 2020)
The society of subcontinent is a miscellany society since a very long time. In this society two sections have always remained prominent on local level. The first community although is little in number but is comprised of advance religions, collective notions and social machinery. The second group is based on many a man who is rather inferior in social status. The mixture of these two groups helped develop indigenous civilization. The third element has developed from such foreign upshot that, adopting serene or violent sources, penetrated the country. The bases of present civilizational inheritance of the subcontinent are taken from these sections. Different civilizations burgeon and develop fairly naturally according to the particular thinking of that people due to the association of these elements. This pattern continued clan after clan. Keeping this in view, the analysis of the effects of this intermingled civilization that came as a result of the relation among the Hinduism, Buddhism, Muslim and the local civilizations in subcontinent is discussed in this article.